Silent Struggles after Sundown: Investigating the Academic Literacy Challenges of Night Class Students In English Language Education - Hestiningrum, Hanif Wira; Kurniawan, Wahyu; iasya, Lubna; Sentana, Yuli Mahmudah; Pangesti, Nesa Riska (Journal of Applied Linguistics and English Education, 2025)
This study explores the academic literacy challenges faced by night class students in English Language Education who also work full-time. Using a qualitative narrative inquiry approach, five students from Universitas PGRI Adi Buana Surabaya shared their experiences navigating English academic reading and writing under the pressure of limited time, cognitive fatigue, and minimal institutional support. The findings reveal that these learners often struggle to comprehend complex texts and structure academic writing, not due to a lack of motivation, but because of structural and emotional constraints. Many rely on coping strategies such as digital tools or peer support, though these are often insufficient for deep learning. The study highlights that current academic systems are not fully responsive to the realities of non-traditional learners. It recommends inclusive literacy support such as flexible feedback mechanisms, evening-based writing clinics, and integrated instruction. This research calls for a shift toward more equitable and empathetic approaches in English language education